Análisis constitucional del monitoreo de cámaras en lugares públicos y privados y su relación con el derecho a la intimidad - Velásquez Espinoza, George Efraín (2023)
An analysis is made on the use of video cameras; and the inconvenience will be studied with respect to the State policy on the use of video surveillance cameras, and the violation of the constitutional principle of the right to privacy, discovering if this right is considered as fundamental, which allows us to define their individuality, whose value should not be sullied either by technology or by law. The relevance of this research work is objectively related to the fact that it has the power to know and regulate the monitoring by means of surveillance cameras, and to obtain as a result to know if due to these processes the right to privacy enshrined in the Constitution of Ecuador would be violated. Likewise, to identify the seriousness, understand and justify if these procedures could be linked to the violation of fundamental rights stipulated in the Constitution of Ecuador. For its methodological development, a survey was conducted among legal professionals, in order to obtain information and opinions on the knowledge of the topic itself, and to receive legal contributions in the same sense. The survey questions focused on the participants' understanding and perception of the interaction between these two elements. Quantitative and qualitative analysis of the data was conducted. The trends and patterns identified in the responses were examined, and interpretations were made based on the theoretical framework and the objectives of the study. Finally, a review was made of Spanish legal doctrine and the jurisprudence pronounced by the Constitutional Court of Spain on issues inherent to the violation of the rights to honor and good name, freedom and the right to privacy